Phase I Study of a Bispecific Ligand-Directed Toxin Targeting CD22 and CD19 (DT2219) for Refractory B-cell Malignancies - Bachanova, Veronika; Frankel, Arthur E.; Cao, Qing; Lewis, Dixie; Grzywacz, Bartosz; Verneris, Michael R.; Ustun, Celalettin; Lazaryan, Aleksandr; McClune, Brian; Warlick, Erica D.; Kantarjian, Hagop; Weisdorf, Daniel J.; et al. (Clinical cancer research, 2015)
Purpose: The novel bispecific ligand-directed toxin (BLT) DT2219 consists of a recombinant fusion between the catalytic and translocation enhancing domain of diphtheria toxin (DT) and bispecific single-chain variable fragments (scFV) of antibodies targeting human CD19 and CD22. We conducted a phase I dose-escalation study to assess the safety, maximum tolerated dose, and preliminary efficacy of DT2219 in patients with relapsed/refractory B-cell lymphoma or leukemia. Experimental Design: DT2219 was administered intravenously over 2 hours every other day for 4 total doses. Dose was escalated from 0.5 μg/kg/day to 80 μg/kg/day in nine dose cohorts until a dose-limiting toxicity (DLT) was observed. Results: Twenty-five patients with mature or precursor B-cell lymphoid malignancies expressing CD19 and/or CD22 enrolled to the study. Patients received median 3 prior lines of chemotherapy and 8 failed hematopoietic transplantation. All patients received a single course of DT2219; one patient was retreated. The most common adverse events, including weight gain, low albumin, transaminitis, and fever were transient grade 1–2 and occurred in patients in higher dose cohorts (≥40 μg/kg/day). Two subjects experienced DLT at dose levels 40 and 60 μg/kg. Durable objective responses occurred in 2 patients; one was complete remission after 2 cycles. Correlative studies showed a surprisingly low incidence of neutralizing antibody (30%). Conclusions: We have determined the safety of a novel immunotoxin DT2219 and established its biologically active dose between 40 and 80 μg/kg/day ×4. A phase II study exploring repetitive courses of DT2219 is planned. Clin Cancer Res; 21(6); 1267–72. ©2015 AACR.